Nyt liv til støvede ordbøger - Troelsgård, Thomas; Sørensen, Nicolai Hartvig (Nordiske Studier i Leksikografi, 2018)
In the current age of digitisation, an increasing number of older diction-aries are accessible to dictionary users. Often these sources escape the at-tention of the modern user, although they could be valuable tools in many situations. There can be several reasons for this: complicated access, poor readability (e.g. a complex entry structure that might work as a deterrent), or just pure coincidence. The Society for Danish Language and Literature has digitised and published a series of historic dictionaries. In this paper, we briefly describe these resources, and we give an account of our attempt to promote them via social media and by connecting the diction-aries to the more popular website of the modern Danish dictionary, Den Danske Ordbog. We argue for a network solution where a lookup is per-formed within a specific dictionary, but with direct links to other relevant dictionaries added. Finally, we outline our plans for future enhancement of the links through manually curated lemma linking across dictionaries.